2008
DOI: 10.1007/s00335-007-9086-5
|View full text |Cite
|
Sign up to set email alerts
|

QTL for the heritable inverted teat defect in pigs

Abstract: The mothering ability of a sow largely depends on the shape and function of the mammary gland. The aim of this study was to identify QTL for the heritable inverted teat defect, a condition characterized by disturbed development of functional teats. A QTL analysis was conducted in a porcine experimental population based on Duroc and Berlin Miniature pigs (DUMI). The significant QTL were confirmed by linkage analysis in commercial pigs according to the affected sib pair design and refined by family-based associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…The average number of inverted teats in affected pigs in our study was 3.1, which is similar to the figures presented in earlier studies in different commercial pig lines (Beilage et al 1996; Clayton et al 1981; Hittel 1984; Jonas et al 2008; Mayer and Pirchner 1995). The study of a larger Swedish Yorkshire cohort reported that in 2010, 13% of the Swedish Yorkshire animals with potential for breeding did have at least one inverted teat at the time point of selection (Chalkias et al 2013).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The average number of inverted teats in affected pigs in our study was 3.1, which is similar to the figures presented in earlier studies in different commercial pig lines (Beilage et al 1996; Clayton et al 1981; Hittel 1984; Jonas et al 2008; Mayer and Pirchner 1995). The study of a larger Swedish Yorkshire cohort reported that in 2010, 13% of the Swedish Yorkshire animals with potential for breeding did have at least one inverted teat at the time point of selection (Chalkias et al 2013).…”
Section: Resultssupporting
confidence: 92%
“…The positions of previously reported QTL for teat traits were compared to our findings. Previously, some of the results shown here had been combined with data from a linkage study (Jonas et al 2008). Microsatellite markers which had not been mapped to the ENSEMBL genome in that study were further located using flanking markers according to the NCBI map-viewer (http://www.ncbi.nlm.nih.gov/projects/mapview/maps.cgi?).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…As to its expansive role in mammary gland development, LEF-1 gene was identified as a candidate gene for teat number trait (Jonas et al, 2008; Tetzlaff et al, 2009). We tested the levels of LEF-1 mRNA in different tissues and the mammary gland at different developmental stages and found extremely high levels in the teat that had a tendency to gradually decrease during growth which suggested its enormous regulatory potential in mammary gland development.…”
Section: Introductionmentioning
confidence: 99%